Penerapan Metode Analytical Hierarchy Process (AHP) Pada Penilaian Pegawai Teladan - Muliawan, Agung; Sabilirrasyad, Iqbal; Fauziah, Difari Afreyna (Puslitbang Akademi Relawan TIK Indonesia, 2024)
One of the factors supporting the success of a business place is productive employees who have maintained and improved qualification standards. The company's appreciation for exemplary employees can be given by giving gifts or awards. Employee performance assessment can be done to determine employees who are qualified and highly dedicated to the company. However, many companies experience difficulties in evaluating employee performance because the calculations are still manual so that they are less effective and objective, one of which is SMK Visi Global Jember. The research will apply the Analytical Hierarchy Process (AHP) method in determining the best employees at SMK Visi Global Jember so that the selection process is right on target with the needs of the criteria given. The required criteria include honesty, loyalty, commitment, discipline and cooperation which will be processed to produce the highest rank for determining recommendations for exemplary employees. The results of this study produce a Consistency Ratio (CR) value of 0.083 so that the value of giving preferences is consistent and can be used in determining exemplary employees at SMK Visi Global Jember